2011
DOI: 10.1073/pnas.1014959108
|View full text |Cite
|
Sign up to set email alerts
|

Cellular copper levels determine the phenotype of the Arg 875 variant of ATP7B/Wilson disease protein

Abstract: In human disorders, the genotype-phenotype relationships are often complex and influenced by genetic and/or environmental factors. Wilson disease (WD) is a monogenic disorder caused by mutations in the copper-transporting P-type ATPase ATP7B. WD shows significant phenotypic diversity even in patients carrying identical mutations; the basis for such diverse manifestations is unknown. We demonstrate that the 2623A/G polymorphism (producing the Gly 875 →Arg substitution in the A-domain of ATP7B) drastically alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 18 publications
(23 reference statements)
5
46
0
Order By: Relevance
“…7 D and D′). Interestingly, the presence of copper appears to promote ATP7B S653Y/858TGE860>AAA exit from the ER, as has been reported for the ATP7B G875R variant (30). We conclude that the S653Y was not dominant in the context of the TGE>AAA mutation.…”
Section: Second-site Mutational Analysis Reveals That the S653y Mutationsupporting
confidence: 53%
See 2 more Smart Citations
“…7 D and D′). Interestingly, the presence of copper appears to promote ATP7B S653Y/858TGE860>AAA exit from the ER, as has been reported for the ATP7B G875R variant (30). We conclude that the S653Y was not dominant in the context of the TGE>AAA mutation.…”
Section: Second-site Mutational Analysis Reveals That the S653y Mutationsupporting
confidence: 53%
“…In addition to the cellular components required for copperdependent ATP7B trafficking, studies have shown that molecular signals within the protein, as well as intramolecular interactions, play important roles (30,40). Two well-characterized trafficking signals encoded within the primary sequences of both copper-ATPases have been identified: (i) F 37 -E 45 in ATP7B, which is required for retention of ATP7B in the TGN (−Cu) and targeting to the apical region in polarized hepatic cells (+Cu, anterograde trafficking) (11); and (ii) di-and trileucines in ATP7A and ATP7B's C-termini, which are needed for retrograde trafficking to the TGN (−Cu) (12,41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed Mutagenesis in ATP7B-The previously generated construct of N-terminally Flag-tagged ATP7B in pcDNA 5.1 FRT/TO vector was used as a template (26). The Ser3 Ala, Ser3 Gly, Ser3 Thr, and Ser3 Asp mutations were introduced by PCR using the Quickchange XL mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…To test this hypothesis, we took advantage of a naturally occurring ATP7B variant ATP7B R875 , which has a low apparent affinity to copper compared with a common ATP7B G875 variant and a very distinct cellular behavior. In basal or low copper, ATP7B R875 localizes in the endoplasmic reticulum (ER), but it traffics to the TGN and then to vesicles when copper is increased in a stepwise fashion (26). Stabilizing the "copper-bound" state for the ATP7B R875 variant is expected to change its localization from ER to TGN and/or vesicles under basal conditions.…”
Section: Mutation Of Ser-340/341 Mimics Consequences Of Copper Binding-mentioning
confidence: 99%